Factors Affecting the Formation of Shadow Economy (Importation of Goods) in Rural Areas of Iran - Anabestani, Aliakbar; Namdar, Mahboubeh (Journal of History Culture and Art Research, 2017)
The economic situation of every village is affiliated to the function of the existing economic sectors in the village (agriculture, industry, services). This article is derived from the field study (case study) in villages in the central part of the Lamerd in the southern province of Fars, in terms of nature, is a kind of exploratory investigation and benefiting from scientific methodologies and using a questionnaire and interview, seeks to find a reasonable solution and answer why and how to expand the formation and activity and its effect on the process of development in the villages of the study. Volume of the sample, according to Cochrane, including 156 families who have been chosen by random sampling method. Results show that the main factors which caused the emergence of this kind of employment and increasing prosperity in the region, can be key factors, including the former and current migration of the inhabitants of the region, to the Persian Gulf countries and high revenues from the employment of people in those countries, appropriate spatial- regional location appropriate access roads and transit routes and the proximity to the south of the country 's booming country and commercial, including Assalouyeh Ports, Bandar Abbas and Bushehr pointed out.